Analisis kualitas pada Proses Pencelupan dengan Metode DMAIC di Departemen Dyeing PT. Indonesia Synthetic Textile Mills - Ristandi, Alvian; Abidin, Abidin (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
In the industrial sector, the large number of companies creates fierce competition. This encourages the company to increase its competition, which can be done through quality improvement. All companies are trying to achieve this, including PT. Indonesia Synthetic Textile Mills. PT. Indonesia Synthetic Textile Mills is a company engaged in the textile industry. In the production process, defective products are still produced. The application of the define, measure, analyze, improve, and control (DMAIC) method found 16 types of defects. A sigma level of 4.34 indicates a fairly good product quality level. Most defects come from six types of defects, namely: kako yogore, kako shiwa, kako atari, iro yogore, atary calender, and friction mark. Defects are caused by man, material, machine, method, environment, and process factors. For quality improvement should be done from defects that most often occur.